The statement of cash flows: direct and indirect method / PM Noryati Md Noor - Md Noor, Noryati (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The statement of cash flows does not always receive the same attention as the other financial statements such as the statement of profit or loss and the statement of financial position. What is a statement of cash flows? How can it contribute to the decisions made? The economic decision made by the users should incorporate an evaluation of the ability of an entity to generate cash and cash equivalent, including the timing and assurance of their generation. There is a need to know the sources and uses of cash, so owner/management can optimize any limited resources.